Augmented reality in customer experience: systematic review - Christian Cervantes; Sussy Bayona-Oré; Nicolás Pintado Torre (Universitas Ahmad Dahlan, 2024)
Augmented reality (AR) is an emerging technology that offers the opportunity to explore a new way of shopping in the customer experience, showcasing its benefits, such as the superimposition of virtual elements in a physical environment or the high degree of interactivity provided by this technology. Despite its great potential to satisfy customer needs, the evaluation of the customer experience has not been fully studied. The main of this study is to identify the constructs that influence customer experience using the systematic review technique. A total of 88 studies published between 2016 and 2021, which relate to customer experience, were identified. Relevant information, such as the definitions of AR and customer experience, and the constructs that various authors use to assess customer experience, was extracted. The results of the review indicate that five fundamental constructs–attitude, interactivity, customer satisfaction, purchase intention, and hedonic value–are used to assess customer experience. These results contribute to a better understanding of the customer experience with AR.